Polyamines accentuate vase life by augmenting antioxidant system in cut spikes of Consolida ajacis (L.) Schur. - Haq,Aehsan ul (2021)
Abstract Postharvest senescence is one of the crucial challenges limiting the marketability of cut flowers. Pertinently, recent investigations implicate extensive role of polyamines in regulation of flower senescence. The present study was envisaged to test the efficacy of poylamines in preserving the postharvest quality of Consolida ajacis (C. ajacis) cut spikes. The cut spikes of C. ajacis were subjected to various treatments of polyamines viz, 4 mM Spermine (SPM), 6mM Putrescine (PUT) and 6 mM Spermidine (SPD). A separate set of spikes held in distilled water represented the control. Our results authenticate a significant improvement in vase life of cut spikes of C. ajacis as compared to control. The increment in vase life was commensurate with the higher concentration of sugars, proteins and phenols in the tepal tissues. Polyamines amplified the activity of various antioxidant enzymes viz, superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX) to overcome the deleterious effects of reactive oxygen species (ROS). The membrane outflow of tepal tissues was profoundly reduced due to attenuated lipoxygenase (LOX) activity. These findings reveal conspicuous role of polyamines particularly SPM in modulation of flower senescence in cut spikes of C. ajacis.